Study on Transorgan Regulation of Intervertebral Disc and Extra-Skeletal Organs Through Exosomes Derived From Bone Marrow Mesenchymal Stem Cells - Wang, Zhikun; Wu, Yangming; Zhao, Zhonghan; Liu, Chengyi; Zhang, Lingli (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are membranous lipid vesicles fused with intracellular multicellular bodies and then released into the extracellular environment. They contain various bioactive substances, including proteins, mRNA, miRNAs, lncRNAs, circRNAs, lipids, transcription factors, and cytokine receptors. Under certain conditions, bone marrow mesenchymal stem cells (BMSCs) can differentiate into osteoblasts, chondrocytes, adipocytes, and biological functions. This study provides a theoretical basis for the application of exosomes derived from bone marrow mesenchymal stem cells (BMSC-Exos) in osteology, exploring different sources of exosomes to improve bone microenvironment and resist bone metastasis. We also provided new ideas for the prevention and rehabilitation of human diseases by exosomes.